Host species and vegetable fruit suitability and preference by the parasitoid wasp Fopius arisanus - Ayelo, P.M.; Sinzogan, A.A.C.; Bokonon-Ganta, A.H.; Karlsson, M.F. (Wiley, 2017)
Parasitoids that oviposit in a concealed host inside a plant part need to be able to find both the plant and the host. Egg parasitoids of fruit-infesting Tephritidae need to assess the oviposition site based both on the host egg and the infested fruit. Infestation by Tephritidae fruit flies threatens fruit and vegetable production. Management methods have been implemented including biological control, using Fopius arisanus Sonan (Hymenoptera: Braconidae). The parasitism by F. arisanus in three Tephritidae flies in vegetable fruits was investigated. Laboratory assays were conducted to assess the parasitoid's preference and survival. Zucchini, sweet pepper, and tomato were artificially infested with eggs of Bactrocera dorsalis Hendel, Ceratitis capitata Wiedemann, and Ceratitis cosyra Walker (all Diptera: Tephritidae), then exposed to mated naïve F. arisanus females in a 20:1 egg:parasitoid ratio. Parasitoid behavioral activities (resting, antennating, probing, ovipositing) were observed on the infested fruits. Parasitism rate was determined by dissection of fruit fly eggs under a stereomicroscope. Behavioral activities of F. arisanus differed between all the fruits when infested with B. dorsalis or C. cosyra eggs but differed only between some of the fruits when infested with C. capitata. Fopius arisanus preferred B. dorsalis over C. capitata and C. cosyra, with a parasitism rate 2× higher on B. dorsalis compared to the Ceratitis species. Preference for fruits was dependent on the infesting fruit fly. The emergence of F. arisanus was higher with B. dorsalis than with Ceratitis spp. Although B. dorsalis completed its development earlier than Ceratitis spp., host fly species did not affect the developmental time of F. arisanus. We discuss the significance of F. arisanus preference in relation to naturally occurring Tephritidae infestations. We also discuss whether some fruits might constitute a refuge for Tephritidae flies and whether this will affect the current biological control efforts against B. dorsalis.